The Duality of Image and Significance in the Single Singular in Rashid Issa's Poetry - Qaralleh, Elham; Al-Btoush, Ibrahim (Dirasat: Human and Social Sciences, 2022)
This study analyzes numerous models of complete sentence forms combined in one word that contain a verb, a subject and an object, or only a verb and a subject , such as Tarrazani’s "embroider me" and Zanbagat "lily", where these formulas are abundantly found in Rashid Issa's poetry, and this phenomenon has become an aesthetic advantage shining in his poetic language, in addition, one of the reasons we sought to identify other structural aspects of the single word that the poet brought to serve the image and the psychological state that brought him to this, such as generating from the rigid, its conjugation and the necessary transgression of verbs, and also his use of formulas that contradict linguistic analogy. To reveal the importance of these technical advantages, the researchers memorized the potential spaces of the poetic image in those universal formulas, and deduced the semantic fields expected in them as well, by relying on the analytical, descriptive, and psychological methods. The researchers concluded that the poet’s use of such words (sentences) was based on what was measured against the words of the Arabs, especially in the field of derivation according to Ibn Jana and others, however, he presented to the Arabic poem a new set of innovative linguistic enriching, such as “sawsantne” from Alsawsanah (lily) , and “Lailakaha” from the lilac star or the lilac flower, and “Tamarimat” from Mary, mother of Jesus, peace be upon him